If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6(x + -2) = 0 Reorder the terms: 2x + -6(-2 + x) = 0 2x + (-2 * -6 + x * -6) = 0 2x + (12 + -6x) = 0 Reorder the terms: 12 + 2x + -6x = 0 Combine like terms: 2x + -6x = -4x 12 + -4x = 0 Solving 12 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -4x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 0 + -12 -4x = 0 + -12 Combine like terms: 0 + -12 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| 5m-2=3m+10 | | (y-4x)/4x=0 | | 36=4(4+4x) | | 7920+X=1000000 | | 2x+(-5)=9 | | 3+4ex=11 | | X-17=28-2x | | (94+84+94+78+78+92+X)/6=90 | | (94+84+94+78+78+92+X)/6=80 | | -4(x+3)+6=6(x+5)+5 | | 0=4x^2-9x-9 | | (94+84+94+78+78+92+X)/8=80 | | 8n+1=17 | | 8/9x1/5= | | Y=23.75x | | 430=0.1x^2+2.4x+25 | | 2=2x+2y | | 170+.61x=332.26 | | (-5/11)^2= | | 30-3k= | | 3-(4y-8)+15=14 | | W-5+2(2w+4)=-3(w+1) | | 5t+20= | | X+5+2x-10=90 | | 6x+2c=3c-(6+5) | | 9=2+d | | Y^2-6y-8= | | -5(-1-5x+5)(-8x-2)=-4x-8x | | -5-1-5x+5(-8x-2)=-4x-8x | | (6.4-2.3)x=73.8 | | -2=-3a+4 | | 152=4(7n+3) |